Erythropoietin supports the survival of prostate cancer, but not growth and bone metastasis. Issue 11 (13th September 2013) - Shiozawa, Yusuke; McGee, Samantha; Pienta, Michael J.; McGregor, Natalie; Jung, Younghun; Yumoto, Kenji; Wang, Jingcheng; Berry, Janice E.; Pienta, Kenneth J.; Taichman, Russell S.
Abstract Erythropoietin (Epo) is used in clinical settings to enhance hematopoietic function and to improve the quality of life for patients undergoing chemotherapy by reducing fatigue and the need for transfusions. However, several meta‐analyses have revealed that Epo treatments are associated with an increased risk of mortality in cancer patients. In this study, we examined the role of Epo in prostate cancer (PCa) progression, using in vitro cell culture systems and in vivo bone metastatic assays. We found that Epo did not stimulate the proliferation of PCa cell lines, but did protect PCa cells from apoptosis. In animal models of PCa metastasis, no evidence was found to support the hypothesis that Epo enhances metastasis. Together, these findings suggest that Epo may be useful for treating severe anemia in PCa patients without increasing metastatic risk. J. Cell. Biochem. 114: 2471–2478, 2013. © 2013 Wiley Periodicals, Inc.